PERANAN MUSIM TERHADAP KESESUAIAN PERAIRAN PESISIR GUGUS PULAU KALEDUPA UNTUK USAHA BUDIDAYA RUMPUT LAUT - Akhmad Mansyur; Rosmawaty Rosmawaty (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2017)
This research aims to determine Daily Growth Rate (LPH) of seaweed in each observation station in East, West and Transmission Season; Obtain a real distance between seaweed LPH in each station in the season average and in each season in the station average; and Obtain the area of each phycoculture area that is classified based on the interaction between daily growth rate, season and station. The method of analysis of seaweed LPH was introduced into a randomized block design and continued with the Duncan multiple distance test used to achieve the first and second goals. Furthermore, a geographic information system analysis method is applied to achieve the third goal. As a result, there is a real distance between LPH seaweed between stations 2 and 11 in one season average. Likewise between the two with several other stations. While between stations 3, 1, 10, 6, 7 and 9 there is no real difference distance. Same with stations 13, 8, 4 and 5, but this group of stations is different from other groups of stations. On the other hand, there is a real distance between LPH in East, Transition and Western Season in station average. LPH is best found in East Season, followed by Transmission, following the West. Based on the interaction between LPH, seasons and stations there is a classification of coastal waters for a well-stable phycoculture (KSB) business of around 2557 ha and a good dominant (KDB) of around 180 ha in a cycle of seasonal changes. The rest, there are around 3209 ha as an area of cultivation that is not yet stable (KSBB).